Suppression of MCM2 reduces cancer stem cells and epithelial-mesenchymal transition-related phenotypes in breast cancer cells - Rae-Kwon Kim (Korean Journal of Clinical Oncology, 2026)
Purpose: Minichromosome maintenance protein 2 (MCM2) is a key regulator of DNA replication and has been implicated in tumor progression. While previous studies have demonstrated its role in lung cancer stem cells (CSCs), its role in breast cancer remains unclear. This study aimed to investigate whether MCM2 regulates CSCs and epithelial-mesenchymal transition (EMT) in breast cancer.Methods: MCM2 expression and its prognostic significance were analyzed using public breast cancer datasets. MDA-MB-231 breast cancer cells were transfected with MCM2-specific small interfering RNA. CSC-associated markers and EMT-related proteins were evaluated by Western blotting. Sphere formation, migration, and invasion assays were performed to assess CSC properties and metastatic potential.Results: MCM2 expression was significantly elevated in breast cancer tissues and correlated with poor prognosis. Knockdown of MCM2 reduced the expression of CSC-associated markers, including ALDH1A1, Sox2, Oct4, and CD44. Functional assays showed that MCM2 suppression significantly decreased sphere-forming capacity, indicating impaired CSC properties. In addition, MCM2 knockdown increased E-cadherin expression while decreasing N-cadherin, Slug, Twist, and ZEB1 expression, suggesting inhibition of EMT. Migration and invasion abilities were also markedly reduced.Conclusion: Suppression of MCM2 was associated with reduced CSC and EMT-related phenotypes in MDA-MB-231 breast cancer cells.